Hopping conductivity in lithium-iron spinel doped with La,Y - Vakalyuk, A.V.; Vakalyuk, V.M.; Pakhovskyi, O.P.; Hasiuk, I.M. (Physics and Chemistry of Solid State, 2025)
The temperature-frequency dependences of the electrical characteristics of Li2Fe2,5-xMexO4 (Ме=La;Y, x=0;0.01;0.03;0.05) spinels synthesized by the «sol-gel» autocombustion technology were obtained by the method of impedance spectroscopy in the temperature range of 293-473 K. Based on their analysis, the main mechanisms of conductivity of these materials in the studied temperature range were identified: hopping and activation. It was shown that at low temperatures the hopping mechanism of conductivity dominates. The main parameters of hopping conductivity have been determined. The effect of doping lithium-iron spinels with rare-earth metal impurities on them has been investigated. Методом імпедансної спектроскопії отримані температурно-частотні залежності електричних характеристик Li2Fe2,5-xМеxO4 (Ме=La;Y, x=0;0,01;0,03;0,05) шпінелей, синтезованих за технологією «золь-гель» автоспалювання, в інтервалі температур 293-473К. На основі їх аналізу виявлені основні механізми провідності цих матеріалів в досліджуваному інтервалі температур: стрибковий та активаційний. Показано, що при низьких температурах домінує стрибковий механізм провідності. Встановлено основні параметри стрибкової провідності. Досліджено вплив на них легування літій-залізних шпінелей доміщками рідкісноземельних металів.